2021
DOI: 10.1186/s13293-021-00379-y
|View full text |Cite|
|
Sign up to set email alerts
|

Network analysis of the left anterior descending coronary arteries in swim-trained rats by an in situ video microscopic technique

Abstract: Background We aimed to identify sex differences in the network properties and to recognize the geometric alteration effects of long-term swim training in a rat model of exercise-induced left ventricular (LV) hypertrophy. Methods Thirty-eight Wistar rats were divided into four groups: male sedentary, female sedentary, male exercised and female exercised. After training sessions, LV morphology and function were checked by echocardiography. The geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 82 publications
(108 reference statements)
0
8
0
Order By: Relevance
“…For the technical implementation of our study, we chose the micropreparation and video-microscopic analysis of the LAD branch system [ 39 , 40 , 41 , 42 ]. The technique allows the whole network to be analyzed in its complexity, using physiological pressure conditions to which the blood vessels respond with their own myogenic tone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For the technical implementation of our study, we chose the micropreparation and video-microscopic analysis of the LAD branch system [ 39 , 40 , 41 , 42 ]. The technique allows the whole network to be analyzed in its complexity, using physiological pressure conditions to which the blood vessels respond with their own myogenic tone.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous work by our research group, we have demonstrated that high blood pressure increases the incidence of these anomalies in the rat LAD network. [ 42 ] In earlier works, we have found that the Murray law of bifurcations was maintained in cases of hypertension, aging and physical exercise [ 39 , 41 ]. In our present study, there was no significant difference between the two groups in terms of the unfavorable coronary anomalies characterizing aged and hypertensive networks [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the main obstacles that tissue engineering must overcome in large-scale clinical applications is the optimal formation of a vascular network that allows the newly created tissue to be easily accepted by the host, and to have network support that allows the perfusion of both oxygen and nutrients and waste elimination (Vu et al, 2022). In this regard, synthesize biomaterials for tissue culture have proven to be excellent for vascular remodeling but their thicknesses of more than 500 µm reduce their application (Ma et al, 2022), as the cells migrate not more than 300 µm from the surface and then they become quiescent due to the low diffusion of oxygen and nutrients (Török et al, 2021).…”
Section: Vascular Remodeling Therapiesmentioning
confidence: 99%